AUF1 Promotes Proliferation and Invasion of Thyroid Cancer via Downregulation of ZBTB2 and Subsequent TRIM58 - Du, Xin; Wang, Jia-Mei; Zhang, Da-Lin; Wu, Tong; Zeng, Xiao-Yan; Jiang, Jing-Yi; Du, Zhen-Xian (Frontiers in Oncology, 2021)
The pathogenesis of papillary thyroid cancer (PTC), the most common type of thyroid cancer, is not yet fully understood. This limits the therapeutic options for approximately 7% of invasive PTC patients. The critical role of AUF1 in the progression of thyroid cancer was first reported in 2009, however, its molecular mechanism remained unclear. Our study used CRISPR/Cas 9 system to knockdown AUF1 in IHH4 and TPC1 cells. We noticed that the expression of TRIM58 and ZBTB2 were increased in the AUF1 knockdown IHH4 and TPC1 cells. When TRIM58 and ZBTB2 were inhibited by small hairpin RNAs (shRNAs) against TRIM58 (shTRIM58) and ZBTB2 (shZBTB2), respectively, the proliferation, migration and invasion ability of the AUF1-knockdown IHH4 and TPC1 cells were increased. In addition, two ZBTB2 binding sites (-719~-709 and -677~-668) on TRIM58 promoter and two AUF1 binding sites (1250-1256 and 1258-1265) on ZBTB2 3’-UTR were identified. These results suggested that AUF1 affecting thyroid cancer cells via regulating the expression of ZBTB2 and TRIM58.